Inquiring with small animals in the primary classroom (Journal of Parents and Teachers, 2013)
This article presents a proposal to study animals and plants from a perspective of investigation in Primary Education. In this study, the students use common samples of animals that are easy to obtain from the environment (snails and worms). The aim of this proposal is that the children acquire and develop new abilities related to investigation and, also, That understands the concept of the construction of an animal, always define by educational science of their level. The activities that they realize are focus in the interactions between the organisms and the environment, more specifically regarding the external morphology and the response to stimulus.
Keywords: Learning activities; Primary education; Living beings; Investigation; Senses; didactic